Design estratégico para processos empreendedores femininos no contexto da moda sustentável - Terra, Juliana Silla (Universidade do Vale do Rio dos Sinos, 2020)
Based on the identification of another way of entrepreneurship with different characteristics from the traditional entrepreneurship and made by women, this research explores the topic female entrepreneurship in a sustainable local context. The research departs from a strategic design point of view with a cultural social innovation approach. In this way, the goal of this research was propose strategic process projects in order to enhance the female entrepreneurship in a sustainable local context. The study started with a theoretical discussion about strategic design, entrepreneurship and entrepreneur processes. Then the relation between those themes was explored in two ways: in a bibliographic research regarding the entrepreneur process of Coco Chanel and Stella McCartney and in interviews with female entrepreneurs. This female entrepreneurs were the subject of this study. They were from the Porto Alegre sustainable fashion context and part of the Ecossistema da Moda Sustentável de Porto Alegre. After the semiotic analysis of the data, the main results found were that the female entrepreneurs put their in their business the change they want to see in the world and conduct it based on their personal values. In addition, from this result this study propose that in a sustainability context the female entrepreneur process is cyclical and composed by six stages. As a result, this study deliver a project proposal. This consists in a toolkit who helps female entrepreneurs on their entrepreneur processes. The main goal of the toolkit is empower this woman and encourage them to assume the role of potential agents of change in social, economic and cultural systems through their personal values and business.
Keywords: Empreendedorismo feminino; Design estratégico; Empoderamento; Empreendedorismo; Female entrepreneurship; Strategic design; Empowerment; Entrepreneurship; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial